2018
DOI: 10.1155/2018/1643906
|View full text |Cite
|
Sign up to set email alerts
|

Association of Cytotoxic T Lymphocyte Antigen-4 Gene Polymorphisms with Psoriasis Vulgaris: A Case-Control Study in Turkish Population

Abstract: Psoriasis is a common, chronic, and autoimmune skin disease in which dysregulation of immune cells, particularly T cells, is thought to play an important role in the pathogenesis. Cytotoxic T lymphocyte antigen-4 (CTLA-4) expressed only on activated T cells is an immunoregulatory molecule and plays a role in the pathogenesis of autoimmune disorders. We aimed to determine whether CTLA-4 gene polymorphisms are associated with development and/or clinical features of psoriasis vulgaris (Pv). Genotyping of SNPs (−3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 74 publications
0
3
0
Order By: Relevance
“…An abundance of T H 17-linked transcripts was immediately apparent. In addition to the known PV markers IL17F and CXCL13 (9), these PV-specific up-regulated DEGs include granulysin GNLY and CTLA4, whose loci have been linked genetically to PV (41,42), KLRB1, which is down-regulated by the tumor necrosis factor- blocker alefacept in psoriatic lesions (43), MGAT4, which is downregulated during ustekinumab treatment of psoriatic arthritis (44), and PIK3R1 whose germline loss of function impairs cutaneous immunity (45). We also detected recurrent overexpression of signaling components such as MAP3K4 and PTPN13 restricted to the Trm1 and Trm3 classes, possibly helping explain why such…”
Section: Distinct Cell Type-specific Patterning Differentiates Forms ...mentioning
confidence: 99%
“…An abundance of T H 17-linked transcripts was immediately apparent. In addition to the known PV markers IL17F and CXCL13 (9), these PV-specific up-regulated DEGs include granulysin GNLY and CTLA4, whose loci have been linked genetically to PV (41,42), KLRB1, which is down-regulated by the tumor necrosis factor- blocker alefacept in psoriatic lesions (43), MGAT4, which is downregulated during ustekinumab treatment of psoriatic arthritis (44), and PIK3R1 whose germline loss of function impairs cutaneous immunity (45). We also detected recurrent overexpression of signaling components such as MAP3K4 and PTPN13 restricted to the Trm1 and Trm3 classes, possibly helping explain why such…”
Section: Distinct Cell Type-specific Patterning Differentiates Forms ...mentioning
confidence: 99%
“…Cytotoxic T-lymphocyte antigen−4 variations have been associated with childhood AD and the severity of AD symptoms, and it can be the initial presenting symptom in 2% of patients . Similarly, CTLA-4 variations have been associated with AA in European populations and psoriasis in Eurasian populations . This case highlights the occurrence of novel immunodeficiency syndromes and alerts dermatologists to the clinical constellation of chronic relapsing skin diseases, frequent respiratory infections, and autoimmune conditions.…”
Section: Discussionmentioning
confidence: 83%
“…Furthermore, the CT60A>G polymorphism may influence the alternative splicing and the generation of soluble CTLA-4 (21). Dursun et al (22) explored the effects of the above three single-nucleotide polymorphisms in the CTLA-4 gene in psoriasis vulgaris patients and healthy volunteers. The results showed that the +49A>G and CT60A>G polymorphisms could be considered as risk factors for the formation of psoriasis vulgaris.…”
Section: Role Of Ctla-4 In Psoriasismentioning
confidence: 99%